Formulation and effectiveness test of Tekelan leaf ethanol extract nanogel preparations against Propionibacterium acnes - Sari, Ratna; Reveny, Julia; Salim, Emil (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Ethanol extract of Tekelan leaves can inhibit the growth of Propionibacterium acnes bacteria. The nanogel preparation can penetrate the deepest layer of the stratum corneum. Utilization of Tekelan leaves in the form of nanogels that have better absorption capabilities with minimal side effects due to the use of natural ingredients is essential to be carried out as an alternative to anti-acne drugs. Methods: This study was conducted experimentally, including the preparation of ethanol extract of Tekelan leaves and formulation in nanogel preparations, which were then tested for antibacterial activity. The concentration of ethanol extract of Tekelan leaves in nanogel preparations were 2.5%, 5%, and 7.5%. Results: The organoleptic of nanogel containing ethanol extract of Tekelan leaves showed that the color was brown and had a distinctive odor, the preparation was homogen, viscosity was still in the required range, pH was still in the required range, 4.5-6.5. The size was below 200 nm, and the cycling test showed that they were stable during storage for six cycles. The nanogel preparations with concentrations of 2.5%, 5%, and 7.5% had diameter inhibitions of 7.93 mm, 9.10 mm, and 10.23 mm, respectively. Conclusions: Based on the study's results, it can be concluded that the nanogel preparation of ethanol extract of tekelan leaves is stable during 12 weeks of storage and has a particle size below 200 nm. The antibacterial test results of nanogel preparations of ethanol extract of tekelan leaves at a concentration of 7.5% have the maximum activity.